Molecular Characterization of a Chrysovirus Isolated From the Citrus Pathogen Penicillium crustosum and Related Fungicide Resistance Analysis - Wang, Shengqiang; Yang, Zhu; Zhang, Tingfu; Li, Na; Cao, Qianwen; Li, Guoqi; Yuan, Yongze; Liu, Deli (Frontiers in Cellular and Infection Microbiology, 2019)
Penicillium sp. are damaging to a range of foods and fruits including citrus. To date, double-stranded (ds)RNA viruses have been reported in most Penicillium species but not in citrus pathogen P. crustosum. Here we report a novel dsRNA virus, designated as Penicillium crustosum chrysovirus 1 (PcCV1) and isolated from P. crustosum strain HS-CQ15. PcCV1 genome comprises four dsRNA segments, referred to as dsRNA1, dsRNA2, dsRNA3 and dsRNA4, which are 3600, 3177, 3078, and 2808 bp in length, respectively. Sequence analysis revealed the presence of four open reading frames (ORFs) in the PcCV1 genome. ORF1 in dsRNA1 encodes a putative RNA-dependent RNA polymerase (RdRp) and ORF2 in dsRNA2 encodes a putative coat protein (CP). The two remaining ORFs, ORF3 in dsRNA3 and ORF4 in dsRNA4, encode proteins of unknown function. Phylogenetic analysis based on RdRp sequences showed that PcCV1 clusters with other members of the genus Chrysovirus, family Chrysoviridae. Transmission electron microscope (TEM) analysis revealed that the PcCV1 visions are approximately 40 nm in diameter. Regarding biological effects of PcCV1, HS-CQ15 harboring the chrysovirus exhibited no obvious difference in colony morphology under fungicide-free conditions but decreased resistance to demethylation inhibitor (DMI)-fungicide prochloraz, as compared to PcCV1-cured strain. Here we provide the first evidence of a virus present in citrus pathogenic fungus P. crustosum and the chrysovirus-induced change in fungicide-resistance of its host fungus.